Advances in production management systems. smart manufacturing for Industry 4.0 : IFIP WG 5.7 International Conference, APMS 2018, Seoul, Korea, August 26-30, 2018, Proceedings /: smart manufacturing for Industry 4.0 : IFIP WG 5.7 International Conference, APMS 2018, Seoul, Korea, August 26-30, 2018, Proceedings. Part II : (2018) - Unknown
No abstract available